Strong sexual selection fails to protect against inbreeding-driven extinction in a moth. (10th June 2021) - Parrett, Jonathan M; Ghobert, Veronica; Cullen, Fenn S; Knell, Robert J
Abstract: Sexual selection is predicted to influence population persistence because skew in male reproductive success may facilitate the purging of mutation load. We manipulated the strength of sexual selection in populations of Indian meal moths, Plodia interpunctella, by adjusting adult sex ratios to be either male- or female-biased, leading to strong and weak sexual selection in males, respectively. After between 19 and 22 generations of experimental evolution, we examined whether mutation load differed between these populations by enforcing successive generations of inbreeding, tracking extinction events, offspring viability and assaying the effect of inbreeding on male mating success and female choice. We found no effect of the strength of sexual selection on the rate of extinction or offspring viability. We did, however, find changes in both male mating success and female choice, with both being influenced by the sex ratio treatment and the number of generations of inbreeding. Males from male-biased populations were more successful at mating with stock females, and mating success declined rapidly with inbreeding regardless of sex ratio treatment. Females from male-biased populations were less likely to mate with stock males at the onset of the experiment, but tended to mate more frequently with increasing inbreeding compared to females from female-biased populations. Our results demonstrate that while mating behaviors have diverged between male-biased and female-biased lines mutation loads remained similar. This suggests that the benefits of sexual selection to population fitness may be low or slow to accumulate under the benign environmental conditions in which these populations evolved. Abstract : Contrary to expectations, a history of strong sexual selection did not protect moth populations against the ill effects of inbreeding. Because competition for mates tends to favor males with fewer deleterious mutations, strong sexual selection should lead to higher average fitness for a population. We tested this in populations of a moth, Plodia interpunctella, which had evolved under weak or strong sexual selection but found no difference in extinction risk when inbreeding was experimentally enforced.